Bible and Women Identity in Post-Colonial Africa - Oderinde, Olatundun Abosede (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The contemporary social and political contexts of the African continent are shaped by its multifaceted histories: pre-colonial, colonial, struggles for independence and post-colonial experiences. The church is not left out in all the stages; shaping and being shaped by these contexts and histories. In all these periods, women have struggled with the issue of identity crisis. One significant factor in African cultures is the way the culture ensures the dependence of women on men for their viability in the community; relationships are structured in such a way that without a man, a woman is handicapped. There has not been much significant change in the identity of women in pre-colonial and post-colonial periods. The study adopted the existential approach to biblical exegesis, using both the advocacy criticism and African Cultural hermeneutics to explore the experiences of women in the bible and post-colonial Africa. The truth is that the woman must define her being; come up with an identity grounded in God, define herself in terms of who she is as a person and not who the society says she is. This paper posits that women must renounce all false identities and discover their real identity as human beings created in the image of God. Keywords: Women identities, Post-Colonial Africa, Culture, Bible